Angelika Neurwirth And Qur'anic Textual Originality (Epistemological Analysis Of Emmanuel Kant's Perspective) - Khairun Niam; Farida Nur Afifah (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This paper reviews Neuwirth's thoughts regarding the originality of the Qur'anic text. According to Neuwirth, the texts of the Qur'an have been considered unoriginal because they have been influenced by Jewish and Christian traditions because the sources and methodologies used still have flaws. In reviewing Neuwirth's thoughts, this research focuses on the epistemology of Angelika Neuwirth's thoughts related to the originality of the Qur'anic text. Departing from the theory used, this paper discusses three questions. First, the sources used by Neuwirth, the methodology used, and how the validity of truth related to the originality of the Qur'anic text according to Neuwirth. This research uses a qualitative method by using library research data collection techniques. The data sources used are primary and secondary. Primary sources of the author get from Neuwirth's writings related to the Qur'an and secondary sources obtained from studies with the same object of study such as journals and books. The data that has been collected will be reduced as needed and analyzed using Emmanuel Kant's epistemology. As for the results of this study, first, Neuwirth uses text sources in the context of late antiquity. Second, Neuwirth uses an intertextuality-based pre-canonization method with a literary and historical approach. This research still has shortcomings, meaning that further research can be carried out related to the epistemology of Neuwirth's angelic thought such as the implications of Neuwirth's thinking for the study of the Qur'an in the West, especially in the scope of scholarship in Indonesia.